VERÃ„NDERUNGEN WORTSTELLUNG DIEÂ UNTERORDNENDEN KONJUNKTIONEN AUF ARTIKEL IN MEDIEN ONLINE SPIEGEL.DE - EKA PUTRI, DIANA (IDENTITAET, 2017)
Texts need cohession and coherent feature in order to be well-estabilished. There is a cohession feature namely conjunction. Conjunction as a cohession feature is important on estabilishment of text. The role of conjunction is to create better understanding for readers (Solich, 2013:12). Nevertheless, the problem  of changing order of conjunction create difficulties for readers to understand the text (McCharty, 1991:155). On choosen articles, there are subordinative conjunctions which postulate this changes. Sentences have diverse pattern on Vorfeld, Satzfeld, and Nachfeld. However, not every part of sentence, especially conjunctions, could take place on them due to specific conditions. Therefore, research question posed in this research is (1) how order of subordinative conjunction on the articles of Spiegel.de and (2) how changes order of subordinative conjunction on the articles of Spiegel.de. This research aimed to (1) describe order of subordinative conjunction on the articles of Spiegel.de and (2) describe changes order of subordinative conjunction on the articles of Spiegel.de. This research use the conjunction and word order according to Heinz Griesbach. This research is qualitatif descriptive research. Documentation technique used to collect data in form of changes of conjunction. Result of this research is order of subordinatif conjunction on six article which published by Spiegel.de is conjunction als as apposition and time, conjunction obwohl, conjunction ob, conjunction damit, conjunction wenn as time and condition, conjunction weil, and conjunction dass. Those conjunction located in Nachfeld and Vorfeld. Subordinative conjunction which  has changes order after permutation is conjunction als as apposition and time located in Satzfeld . Keywords: online articles, subordinative conjunction, word order.